Load Measurement of the Cervical Vertebra C7 and the Head of Passengers of a Car While Driving across Uneven Terrain - Svoboda, Martin; Chalupa, Milan; Jelen, Karel; Lopot, František; Kubový, Petr; Sapieta, Milan; Krobot, Zdeněk; Suszyński, Marcin (Sensors (Basel, Switzerland), 2021)
The article deals with the measurement of dynamic effects that are transmitted to the driver (passenger) when driving in a car over obstacles. The measurements were performed in a real environment on a defined track at different driving speeds and different distributions of obstacles on the road. The reaction of the human organism, respectively the load of the cervical vertebrae and the heads of the driver and passenger, was measured. Experimental measurements were performed for different variants of driving conditions on a 28-year-old and healthy man. The measurement's main objective was to determine the acceleration values of the seats in the vehicle in the vertical movement of parts of the vehicle cabin and to determine the dynamic effects that are transmitted to the driver and passenger in a car when driving over obstacles. The measurements were performed in a real environment on a defined track at various driving speeds and diverse distributions of obstacles on the road. The acceleration values on the vehicle's axles and the structure of the driver's and front passenger's seats, under the buttocks, at the top of the head (Vertex Parietal Bone) and the C7 cervical vertebra (Vertebra Cervicales), were measured. The result of the experiment was to determine the maximum magnitudes of acceleration in the vertical direction on the body of the driver and the passenger of the vehicle when passing a passenger vehicle over obstacles. The analysis of the experiment's results is the basis for determining the future direction of the research.
Keywords: dynamic load; Humans; car; experiment; automobily; zrychlení; dospělí; Automobile Driving; Automobiles; lidé; dopravní nehody; Adult; human; řízení motorových vozidel; Accidents, Traffic; Male; Acceleration; measurement; Cervical Vertebrae; mužské pohlaví; krční obratle